Intrinsic competition between two European egg parasitoids of the brown marmorated stink bug. (17th July 2020) - Stahl, Judith M.; Babendreier, Dirk; Foti, Maria Cristina; Colazza, Stefano; Haye, Tim
Abstract: Following the accidental introduction and spread of the invasive polyphagous agricultural pest Halyomorpha halys (Stål) (Hemiptera: Pentatomidae), the two European egg parasitoids Anastatus bifasciatus (Geoffroy) (Hymenoptera: Eupelmidae) and Ooencyrtus telenomicida (Vassiliev) (Hymenoptera: Encyrtidae) have been investigated for inundative biological control. Since the competititve outcome between the two generalist parasitoids is difficult to predict, intrinsic competition was investigated with a time‐course development study. Both species readily oviposited in H. halys eggs containing eggs and early instar larvae of the competitor, but oviposition decreased when eggs contained late instar larvae and pupae. Ooencyrtus telenomicida offspring emergence from multiparasitized eggs was significantly lower than that from rearing controls, independent of the order of parasitization. Anastatus bifasciatus offspring emergence was not influenced by the presence of O. telenomicida when it parasitized as the first species, but emergence was decreased after oviposition in eggs containing O. telenomicida larvae and pupae. There was no indication that O. telenomicida can act as a facultative hyperparasitoid of A. bifasciatus . These results suggest that A. bifasciatus is the superior intrinsic competitor and no or minor negative implications for A. bifasciatus are expected if released in combination with O. telenomicida .